Economic Growth and Institutional Quality: Empirical Proof from selected SADC and ECOWAS Nations - Susan Felix-Ashakah (International Journal of Sustainable Business, Management and Accounting, 2025)
Background of study: Institutional mechanisms play a critical role in strengthening corporate governance and improving firm transparency and accountability. In emerging markets, the effectiveness of institutional oversight remains a key concern due to information asymmetry, weak monitoring, and inconsistent governance practices. Understanding how institutional factors influence corporate behavior is therefore essential to support sustainable business performance. Aims and scope of paper: This paper aims to examine the influence of institutional factors on corporate governance outcomes and firm performance within the context of sustainable business and accounting practices. The scope of the study focuses on publicly listed companies in Indonesia, emphasizing the role of institutional involvement in enhancing monitoring quality, transparency, and long-term value creation. Methods: The study employs a quantitative research design using secondary data obtained from published annual reports and financial statements. The sample was selected through purposive sampling based on data availability and institutional ownership criteria. Panel data regression analysis was applied to test the proposed relationships, supported by classical assumption tests to ensure the robustness of the model. Result: The empirical findings indicate that institutional involvement has a significant effect on corporate governance quality and firm performance. Higher levels of institutional monitoring are associated with improved transparency, reduced agency problems, and more effective managerial decision-making. Conclusion: This study concludes that institutional mechanisms serve as an important governance tool in promoting sustainable corporate performance. Strengthening institutional oversight can enhance accountability and support long-term business sustainability, particularly in emerging market environments.